IgG Anti-Spike Antibodies and Surrogate Neutralizing Antibody Levels Decline Faster 3 to 10 Months After BNT162b2 Vaccination Than After SARS-CoV-2 Infection in Healthcare Workers - Decru, Bram; Van Elslande, Jan; Steels, Sophie; Van Pottelbergh, Gijs; Godderis, Lode; Van Holm, Bram; Bossuyt, Xavier; Van Weyenbergh, Johan; Maes, Piet; Vermeersch, Pieter (Frontiers in Immunology, 2022)
BACKGROUND: IgG anti-spike (S) antibodies arise after SARS-CoV-2 infection as well as vaccination. Levels of IgG anti-S are linked to neutralizing antibody titers and protection against (re)infection. Understanding long-term antibody kinetics is relevant to estimate protection on an individual and population level METHODS: We measured IgG anti-S and surrogate neutralizing antibody kinetics against wild type (WT) and 4 VOC in health care workers (HCW) 3 and 10 months after natural infection (“infection”, n=83) or vaccination (2 doses of BNT162b2) with (“hybrid immunity”, n=17) or without prior SARS-CoV-2 infection (“vaccination”, n=97). RESULTS: The humoral immune response in the “vaccination” cohort was higher at 3 months, but lower at 10 months, compared to the “infection” cohort due to a faster decline. The “hybrid immunity” cohort had the highest antibody levels at 3 and 10 months with a slower decline compared to the “vaccination” cohort. Surrogate neutralizing antibody levels (expressed as %inhibition of ACE-2 binding) showed a linear relation with log10 of IgG anti-S levels against wild-type and four VOC. IgG anti-S levels corresponding to 90% inhibition ranged from 489 BAU/mL for WT to 1756 BAU/mL for beta variant. CONCLUSIONS: Hybrid immunity resulted in the strongest humoral immune response. Antibodies induced by natural infection decreased more slowly than after vaccination, resulting in higher antibody levels at 10 months compared to vaccinated HCW without prior infection. There was a linear relationship between surrogate neutralizing activity and log10 IgG anti-S levels for WT and 4 VOC, although some VOC showed reduced sensitivity to neutralization.